2002
DOI: 10.1101/gad.970702
|View full text |Cite
|
Sign up to set email alerts
|

SMC1 is a downstream effector in the ATM/NBS1 branch of the human S-phase checkpoint

Abstract: Structural maintenance of chromosomes (SMC) proteins (SMC1, SMC3) are evolutionarily conserved chromosomal proteins that are components of the cohesin complex, necessary for sister chromatid cohesion. These proteins may also function in DNA repair. Here we report that SMC1 is a component of the DNA damage response network that functions as an effector in the ATM/NBS1-dependent S-phase checkpoint pathway. SMC1 associates with BRCA1 and is phosphorylated in response to IR in an ATM-and NBS1-dependent manner. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
349
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(374 citation statements)
references
References 41 publications
20
349
0
Order By: Relevance
“…Several studies showed that the expression of S343A mutant Nbs1 in NBS cells resulted in partial defects in IR-induced S-phase checkpoint activation, radiosensitivity and partial defects in ATM-dependent phosphorylation events including Chk2, SMC1 and FANCD2 (Lim et al, 2000;Buscemi et al, 2001;Nakanishi et al, 2002;Yazdi et al, 2002). Our studies also showed that the MRN complex containing mutant Nbs1 (S343A) failed to stimulate the phosphorylation of Chk2 by ATM although p53 phosphorylation was normal in vitro.…”
Section: Phosphorylation Of Nbs1supporting
confidence: 51%
See 1 more Smart Citation
“…Several studies showed that the expression of S343A mutant Nbs1 in NBS cells resulted in partial defects in IR-induced S-phase checkpoint activation, radiosensitivity and partial defects in ATM-dependent phosphorylation events including Chk2, SMC1 and FANCD2 (Lim et al, 2000;Buscemi et al, 2001;Nakanishi et al, 2002;Yazdi et al, 2002). Our studies also showed that the MRN complex containing mutant Nbs1 (S343A) failed to stimulate the phosphorylation of Chk2 by ATM although p53 phosphorylation was normal in vitro.…”
Section: Phosphorylation Of Nbs1supporting
confidence: 51%
“…The Mre11/Rad50/Nbs1 (MRN) complex has been shown by several groups to be required for the ATM signaling pathway (Lim et al, 2000;Buscemi et al, 2001;Girard et al, 2002;Nakanishi et al, 2002;Yazdi et al, 2002;Uziel et al, 2003). Most of these studies were performed using cells derived from patients with Nijmegen Breakage Syndrome (NBS) or Ataxia-TelangiectasiaLike-Disorder (ATLD), which are caused by hypomorphic alleles of the Nbs1 or Mre11 genes, respectively (Carney et al, 1998;Varon et al, 1998;Stewart et al, 1999).…”
Section: The Role Of the Mrn Complex In Atm Activationmentioning
confidence: 99%
“…Once phosphorylated, NBN promotes the ATMmediated phosphorylation of SMC1 (at residues Ser957 and Ser966) and p53 (at the Ser15 residue). Notably, SMC1 is involved in the activation of the intra-S cell cycle checkpoint and in the entry into mitosis, while p53 regulates the G1/S checkpoint (49)(50)(51). Data obtained indicate that the proper orientation and integrity of the tandem BRCT domains of NBN seems to be crucial for the activation of both ATM and its downstream effectors.…”
Section: Discussionmentioning
confidence: 92%
“…Specific phosphorylation of Nbs1 on S287 and S343 plays a role in the activation of the intra-S-phase checkpoint (Lim et al, 2000). Yazdi et al (2002) showed that ATMdependent phosphorylation of Nbs1 was required for phosphorylation of SMC1, implying that Nbs1, presumably as part of the MRN complex, was an adaptor in an ATM/Nbs1/SMC1 pathway controlling the S-phase checkpoint. An adaptor role for phosphorylated Nbs1 has also been demonstrated in DNA-damage-induced suppression of Tousled-like kinase activity (Krause et al, 2003).…”
Section: Perspectivementioning
confidence: 99%